Brain functional connectivity in individuals with callosotomy and agenesis of the corpus callosum: A systematic review. (October 2019) - Mancuso, Lorenzo; Uddin, Lucina Q.; Nani, Andrea; Costa, Tommaso; Cauda, Franco
Graphical abstract: Highlights: When the corpus callosum is absent, the interhemispheric connectivity is impaired. Surgical transection leads to more severe impairments than congenital agenesis. In any case, some degree of interhemispheric connectivity is preserved. Subcortical structures seem to connect hemispheres in absence of major commissures. A model reminiscent to Sperry's Y-shaped model of consciousness is proposed. Abstract: In the absence of the corpus callosum due to either surgical transection or congenital agenesis, the interhemispheric exchange of information is disrupted, as emphasized by several clinical studies. In such cases, a reduction of interhemispheric functional connectivity, that is, an increased independence of the functional signals of the two disconnected hemispheres, is expected to occur. A growing literature has investigated this hypothesis, and a number of studies were able to confirm it. However, this increased independence is not always observed, especially in congenital agenesis, in which the functional signals of the two hemispheres are often found to be characterized by synchronization or correlation. The extent of these counterintuitive findings and possible explanations are discussed. Overall, these findings highlight both methodological and theoretical considerations that emphasize the importance of subcortical structures, the preservation of which may underlie alternative pathways of functional connectivity and interhemispheric communication.